PENGARUH CITA RASA, LOKASI, KEBERAGAMAN PRODUK, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA KEDAI BABEH DI KENDIT SITUBONDO - Vicky Al Hidayah; Riska Ayu Pramesthi; Muhammad Iqbal Anshory (Jurnal Mahasiswa Entrepreneurship (JME), 2026)
The food and beverage business sector is one of the fields that continues to experience significant growth along with the increasing level of competition among business actors. In order to survive and excel in such competition, business owners need to have a thorough understanding of the factors that influence consumers in making purchasing decisions and shaping their satisfaction. This study aims to identify and analyze the effect of Taste, Location, Product Diversity, and Service Quality on Consumer Satisfaction through Purchase Decision as a mediating variable at Kedai Babeh located in Kendit District, Situbondo Regency. The population in this study includes all consumers of Kedai Babeh, with the sample determined using purposive sampling technique. Data analysis and testing were carried out using the SmartPLS 3.0 application. The results of hypothesis testing for direct effects indicate that Taste has a positive but insignificant effect on Purchase Decision, while Location, Product Diversity, and Service Quality each proved to have a positive and significant effect on Purchase Decision. Meanwhile, Taste and Service Quality have a positive but insignificant effect on Consumer Satisfaction, Location shows a negative and insignificant effect on Consumer Satisfaction, while Product Diversity and Purchase Decision proved to have a positive and significant effect on Consumer Satisfaction. As for the indirect effect testing results, it reveals that Taste and Location have a positive but insignificant effect on Consumer Satisfaction through Purchase Decision, while Product Diversity and Service Quality both proved to have a positive and significant effect on Consumer Satisfaction through Purchase Decision as the mediating variable.